Pengaruh Inventory Intensity, Karakter Eksekutif, Karakteristik CEO Terhadap Tax Avoidance pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) pada Tahun 2016-2020 - Dudi Pratomo; Muhamad Rafki Nazar; Rifqi Aziz Pratama (Universitas Batanghari Jambi, 2022)
Tax avoidance avoidance is an effort by taxpayers to reduce the amount of tax payable without violating the applicable tax provisions by exploiting the weaknesses listed in the Taxation Law and Regulations. In Indonesia, it is very possible for taxpayers to reduce the tax burden, because the tax collection system in Indonesia uses a self-assessment system. This study aims to analyze and examine the effect of Inventory Intensity, Executive Character, CEO Tenure, and CEO Narcissism on Tax Avoidance in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. The sampling technique used was purposive sampling and obtained 42 sample companies with a period of 5 (five) years so that 210 samples were obtained in this study. The data analysis method in this study is panel data regression analysis using the software Eviews 10. Based on the results of this study, it was found that the Inventory Intensity, Executive Character, CEO Tenure, and CEO Narcissism variables simultaneously influence tax avoidance. While partially Inventory Intensity and Executive Character have a positive effect on Tax Avoidance, meanwhile CEO Tenure and CEO Narcissism have no effect on Tax Avoidance.